DESAIN KURIKULUM SEKOLAH ISLAM TERPADU (Studi Kasus di SMPIT Insan Kamil Sidoarjo) - Rojii, Muhammad; Istikomah, Istikomah; Aulina, Choirun Nisak; Fauji, Imam (JURNAL AL-TANZIM, 2019)
Integrated Islamic School is a school whose curriculum integrates Islamic values, skills and national curriculum. The purpose of this research is to describe curriculum design in integrated Islamic schools by taking a research site at SMPIT Insan Kamil Sidoarjo. This research uses a qualitative approach with case study. The research data obtained from interviews, observations, and documentation, then analyzed by reducing data, presenting data, and making conclusions. The results showed that the curriculum design in SMPIT Insan Kamil Sidoarjo emphasized the internalization of Islamic values in every national curriculum content, without overriding the national curriculum set by the Ministry of Education. The assessment process is the main objective created in the learning environment and the content of teaching materials that are loaded with Islamic values. While the purpose of the curriculum design is, so that students have a strong foundation of religious education, which boils down to the strength of aqeedah and moral perfection. Internalization of Islamic values in integrated Islamic schools is not only done through the subjects taught, but through the design of school activities programs that support the inculcation of Islamic values in students.